2019
DOI: 10.1002/anie.201908658
|View full text |Cite
|
Sign up to set email alerts
|

Charging OBO‐Fused Double [5]Helicene with Electrons

Abstract: Chemical reduction of OBO-fused double-[5]helicene with Group 1m etals (Na and K) has been investigated for the first time.T wo doubly-reduced products have been isolated and structurally characterized by singlecrystal X-ray diffraction, revealing as olvent-separated ion triplet (SSIT) with Na + ions and acontact-ion pair (CIP) with K + ion. As the key structural outcome,t he X-ray crystallographic analysis discloses the consequences of adding two electrons to the double helicene core in the SSIT without metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
26
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 79 publications
3
26
0
1
Order By: Relevance
“…Similarly, each K + ion has two coordinated THF molecules (K/O THF , 2.687(8) and 2.699(9)Å), with all K/C and K/O distances being comparable to those previously reported. 8,62,63,66,67 In the solid-state structure of 2, additional K/C contacts (3.102(11)-3.309(11)Å) are found between the external K + ions and the exterior p-surface of the adjacent 1 4anions (Fig. 2).…”
Section: Resultsmentioning
confidence: 98%
“…Similarly, each K + ion has two coordinated THF molecules (K/O THF , 2.687(8) and 2.699(9)Å), with all K/C and K/O distances being comparable to those previously reported. 8,62,63,66,67 In the solid-state structure of 2, additional K/C contacts (3.102(11)-3.309(11)Å) are found between the external K + ions and the exterior p-surface of the adjacent 1 4anions (Fig. 2).…”
Section: Resultsmentioning
confidence: 98%
“…Each K + ion is fully wrapped by two benzo-15-crown-5 ether molecules with the K/O crown distances (2.752(2)-2.945(2) A) being comparable to those previously reported. [51][52][53][55][56][57][58] Seven interstitial THF molecules are found to ll the structural voids with no close contacts.…”
Section: Crystal Structures and Supramolecular Packingmentioning
confidence: 97%
“…Moreover, charging non-planar PAHs with electrons along with investigation of their electronic and structural responses [10] showed that redox processes are topology-and charge-dependent. Extensive Xray diffraction studies of electron transfer for carbon bowls, [11] belts, [12] wires, [13] and helicenes [14] revealed unusual reactivity, unique metal binding and remarkable supramolecular assem-bly patterns of the negatively charged p-systems, thus prompting a broad exploration of novel curved nanocarbon frameworks.…”
mentioning
confidence: 99%